Evaluasi Kualitas Jaringan Internet Pemerintah Daerah Kota Padang Panjang Menggunakan Metode Quality of Service - Indah Permata Sari (Jurnal Sistim Informasi dan Teknologi, 2022)
The Internet network during a pandemic as it is today is the main actor in all aspects. For example, obtaining information, economics, offices, education, and many more. On September 20, 2021, the City of Padang Panjang is included in the Level 3 area, sourced from the circular letter of the Minister of Home Affairs number 44 of 2021 concerning the implementation of restrictions on community activities at level 4, level 3, level 2, and level 1. level 3. 50% of the total number of employees in an office must be WFH (Work From Home) where employees continue to work as usual but stay at home. Then in the field of education 50% of students and teachers carry out online learning or lectures. From the explanation above, it has been illustrated how important a network is today. Employees can continue to work only from home by relying on the Internet Network. Students and students can still get an education even if they don't go to school and campus. And the Internet network plays a big role in that. Padang Panjang City currently has a Smart City program